FKBP12.6 protects heart from AngII‐induced hypertrophy through inhibiting Ca2+/calmodulin‐mediated signalling pathways in vivo and in vitro. Issue 7 (22nd April 2018) - Xiao, Yun‐Fei; Zeng, Zhi‐Xiong; Guan, Xiao‐Hui; Wang, Ling‐Fang; Wang, Chan‐Juan; Shi, Huidong; Shou, Weinian; Deng, Ke‐Yu; Xin, Hong‐Bo
Abstract: We previously observed that disruption of FK506‐binding protein 12.6 (FKBP12.6) gene resulted in cardiac hypertrophy in male mice. Studies showed that overexpression of FKBP12.6 attenuated thoracic aortic constriction (TAC)‐induced cardiac hypertrophy in mice, whereas the adenovirus‐mediated overexpression of FKBP12.6 induced hypertrophy and apoptosis in cultured neonatal cardiomyocytes, indicating that the role of FKBP12.6 in cardiac hypertrophy is still controversial. In this study, we aimed to investigate the roles and mechanisms of FKBP12.6 in angiotensin II (AngII)‐induced cardiac hypertrophy using various transgenic mouse models in vivo and in vitro. FKBP12.6 knockout (FKBP12.6 −/− ) mice and cardiac‐specific FKBP12.6 overexpressing (FKBP12.6 TG) mice were infused with AngII (1500 ng/kg/min) for 14 days subcutaneously by implantation of an osmotic mini‐pump. The results showed that FKBP12.6 deficiency aggravated AngII‐induced cardiac hypertrophy, while cardiac‐specific overexpression of FKBP12.6 prevented hearts from the hypertrophic response to AngII stimulation in mice. Consistent with the results in vivo, overexpression of FKBP12.6 in H9c2 cells significantly repressed the AngII‐induced cardiomyocyte hypertrophy, seen as reductions in the cell sizes and the expressions of hypertrophic genes. Furthermore, we demonstrated that the protection of FKBP12.6 on AngII‐induced cardiac hypertrophy was involved in reducing the concentration of intracellular Ca 2+ ([Ca 2+ ]i), in which the protein significantly inhibited the key Ca 2+ /calmodulin‐dependent signalling pathways such as calcineurin/cardiac form of nuclear factor of activated T cells 4 (NFATc4), calmodulin kinaseII (CaMKII)/MEF‐2, AKT/Glycogen synthase kinase 3β (GSK3β)/NFATc4 and AKT/mTOR signalling pathways. Our study demonstrated that FKBP12.6 protects heart from AngII‐induced cardiac hypertrophy through inhibiting Ca 2+ /calmodulin‐mediated signalling pathways.